2017
DOI: 10.1021/acs.macromol.7b02287
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Properties and Self-Healing Behavior of Ionically Modified Poly(isobutylene-co-isoprene) Rubber

Abstract: The focus of this work is on the nature of selfhealing of ionically modified rubbers obtained by reaction of brominated poly(isobutylene-co-isoprene) rubber (BIIR) with various alkylimidazoles such as 1-methylimidazole, 1-butylimidazole, 1-hexylimidazole, 1-nonylimidazole, and 1-(6chlorohexyl)-1H-imidazole. Based on stress−strain and temperature dependent DMA measurements, a structural influence of the introduced ionic imidazolium moieties on the formation of ionic clusters and, as a consequence, on the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 43 publications
(105 reference statements)
1
88
0
Order By: Relevance
“…This large enhancement showed the remarkably toughened mechanical performance of the network after crosslinking by high‐density iron(III)‐carboxylate clusters. The toughening mechanism was attributed to the secondary high‐affinity ionic bonding of the iron(III)‐carboxylate complexes (Figure B) . The toughened poly(TA‐DIB‐Fe) network with an iron(III)‐to‐TA molar ratio of 1/100 exhibited typical rate‐dependent tensile curves (Figure C), in which the sample can be stretched to over 6500 % of original length (Figure D) at a lower strain rate of 20 mm min −1 .…”
Section: Figurementioning
confidence: 99%
“…This large enhancement showed the remarkably toughened mechanical performance of the network after crosslinking by high‐density iron(III)‐carboxylate clusters. The toughening mechanism was attributed to the secondary high‐affinity ionic bonding of the iron(III)‐carboxylate complexes (Figure B) . The toughened poly(TA‐DIB‐Fe) network with an iron(III)‐to‐TA molar ratio of 1/100 exhibited typical rate‐dependent tensile curves (Figure C), in which the sample can be stretched to over 6500 % of original length (Figure D) at a lower strain rate of 20 mm min −1 .…”
Section: Figurementioning
confidence: 99%
“…Ionic interactions can be introduced into rubbers through the ion–dipole interactions among the ionizable groups of polymer chains such as carboxylate, sulfonate, and phosphonate. The aggregation of the ionic clusters acts as physical crosslinks responsible for enhanced flexibility, toughness, temperature sensitivity, and potential self‐healing function . When ionic compounds, such as zinc dimethacrylate were introduced into natural rubbers, or were formed in situ through a well‐controlled peroxide induced graft‐polymerization, the resultant ionic crosslinks form a reversible supramolecular crosslinking network in the rubber matrix and lead to a nearly complete recovery of the mechanical properties after a self‐healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐metallic cations can also be introduced to rubber matrix to form ionic crosslinks. When some nitrogen‐containing compounds, such as alkylimidazoles, 4‐ethyl‐4‐methyl morpholinium methylcarbonate, and 2‐(dimethyl amino)‐ethyl methacrylate were introduced into poly(isobutylene‐co‐isoprene) rubber or acrylate rubber, excellent mechanical and self‐healing performance were obtained, for example, a healed tensile strength of 10.7 MPa (healing efficiency of 74%) and a elongation at break of 1040% (healing efficiency of 98%) . In addition to forming an ionic crosslinking network, metal ions can also be utilized to form supramolecular networks through metal–ligand interactions in rubber matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Ionically modied bromobutyl rubber (BIIR-i) was obtained by conversion of BIIR with 1 (see Scheme 1) as described earlier. 19,20 1-Butyl-3-(trimethoxysilylpropyl)imidazolium bromide (A 2 )…”
Section: Methodsmentioning
confidence: 99%
“…This kind of modication was rst described by Parent et al 17,18 In our own work, we have recently demonstrated that such modied rubbers show a pronounced tendency to self-heal. 19,20 This self-healing effect was attributed to the formation and rearrangement of ionic clusters. Introduction of carbon nanotubes into BIIR-i facilitated self-healing by Joule heating.…”
Section: Introductionmentioning
confidence: 99%